The use of Technological Resources: An investigation of Ad Avoidance Online among Young Adults - Meina, Makarious (2014)
This dissertation examines advertising avoidance and attempt to discover why advertising avoidance software is used or not used in the online world. Our discoveries support many that have been published by previous authors. These include reasons why people use online Adblocking software and avoid ads in general like Convenience, Clutter and Intrusiveness among many other supported findings. However in contrast to previous research this study revealed that people disable or turn off their adblocking software to view ads purposefully in an attempt to support websites and personalities they enjoy online.